MODEL SISTEM INFORMASI GEOGRAFIS UNTUK ESTIMASI KOEFISIEN ALIRAN DAN HUBUNGANNYA DENGAN TUTUPAN LAHAN DI DAS RIAM KANAN PROVINSI KALIMANTAN SELATAN - Rahman, Abdur (Bumi Lestari; Vol 13 No 1 (2013), 2013)
Abstract Simple approach to estimate watershed runoff coefficient value is needed model to forecast problem of demage and watershed and hydrology data problem. Have happened degradation of energy support in Riam Kanan Sub Watershed which critical of landcover impact. This research aims are to estimation surface runoff and distribution in Watershed of Riam Kanan based on Landsat7 ETM+ Imagery. The Research found that the accuracy test using Landsat7 ETM+ image aqual to 87 %, indicates that it has a high accuration to detect of landcover. The results of overlay raster data from landcover parameter was obtained by distribution pattern of runoff coefficient dominated normal class aqual to 61,94 percent, low class aqual to 0,53 percent and high class aqual to 78,14 percent distributed at up stream and middle of Riam Kanan Sub Watershed. Result of statistical test indicated that result of C estimation do not different with result of C actual at significant 95% with enough, mean accuration equal to 78,14 %.
Keywords: Keywords : runoff coefficient, landcover, Landsat7 ETM+ imagery, Cook